2005
DOI: 10.1207/s15327930pje8001_5
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Corruption in Higher Education

Abstract: This article explores the phenomenon of corruption that has become common in higher education in developing countries around the world. Cases of educational corruption include, among others, paying bribes for grades, buying diplomas, and admissions to universities. An available body of literature on educational corruption does not provide sufficient insight on the nature and structure of the phenomenon. This article attempts to fill in the gaps by developing the taxonomy of corruption in higher education. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 6 publications
1
48
0
4
Order By: Relevance
“…Cheung and Chan [44] found that as more people attend tertiary education the lower its impact of corruption across countries, being argued that students recognize the importance of social responsibility and morality through the knowledge they gather in higher education. Moreover, higher education should be seen as a moral enterprise that provides knowledge and experience to students in order to undertake ethical responsibilities and preserve their value correctness [45]. In the long run, there was uncovered that high levels of education corruption are detrimental towards total factor productivity through decreasing the level of human capital and reducing the rate of its accumulation [46].…”
Section: The Impact Of Business Environment On Sustainable Economic Gmentioning
confidence: 99%
“…Cheung and Chan [44] found that as more people attend tertiary education the lower its impact of corruption across countries, being argued that students recognize the importance of social responsibility and morality through the knowledge they gather in higher education. Moreover, higher education should be seen as a moral enterprise that provides knowledge and experience to students in order to undertake ethical responsibilities and preserve their value correctness [45]. In the long run, there was uncovered that high levels of education corruption are detrimental towards total factor productivity through decreasing the level of human capital and reducing the rate of its accumulation [46].…”
Section: The Impact Of Business Environment On Sustainable Economic Gmentioning
confidence: 99%
“…All of these forms of corruption might influence the students' values, beliefs, and lives, either directly or indirectly (Rumyantseva, 2005). In spite of the fact that corruption in higher education has a long history − the first reported cases of mishandled test scores date as far back as the time of the Ch'ing dynasty in China in 1644 − the wave of global attention it is currently experiencing only began in the 1990s (Heyneman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some believe that corruption in education differs somewhat from the issue and nature of corruption in general (Hallack & Poisson, 2001, p. 58), which has prompted efforts to develop taxonomy of corruption (Rumyantseva, 2005). Corruption has been broken down to specific services/functions-in selection, in accreditation, in procurement, skimming from project grants, private tutoring, selling admissions and grades, ghost teachers, influencing personnel appointments, professional misconduct, in educational property and taxes.…”
Section: Corruption In Education: a Theoretical Perspectivementioning
confidence: 99%